Case Report: Introducing @tension—a system for improving adherence to exposure therapy in chronic pain patients - Berkowitz, Shifra; Sivan Speier, Keren; Bartur, Gadi; Fortinsky, Hadassah; Auerbach Lawee, Bracha; Shahaf, Goded (Frontiers in Human Neuroscience, 2026)
Exposure therapy is an effective treatment approach for chronic pain that depends on patient adherence. However, it may evoke fear of pain and even flare-ups, which may lead to non-adherence to the therapy. More specifically, the @tension (pronounced At tension) system aims to provide “protected” graded exposure to assist patients who might otherwise not adhere to exposure therapy. @tension includes real-time monitoring of the patient’s discomfort and attention during graded exposure therapy, and provides online feedback indicating potential increases in discomfort due to pain or stress, which may indicate a good time to pause the exposure for a while, and then resume practice once the patient is ready again. After initial advancement, patients are encouraged to continue the exposure without pauses and to employ techniques to calm the evolving pain. The purpose of this article is to present the @tension system and to demonstrate its potential for assisting patients with chronic pain using representative case reports of patients who encountered difficulties adhering to exposure therapy before using the system. We believe the @tension system may be of potential interest to clinicians and researchers in the field and will be happy to provide the software and needed support.